2011
DOI: 10.1088/0022-3727/44/34/345502
|View full text |Cite
|
Sign up to set email alerts
|

Process characteristics of fibre-laser-assisted plasma arc welding

Abstract: Abstract. Experimental and theoretical investigations on fibre-laser assisted plasma arc welding (LAPW) have been performed. Welding experiments were carried out on aluminium and steel sheets. In case of a highly focused laser beam and a separate arrangement of plasma torch and laser beam, high-speed video recordings of the plasma arc and corresponding measurements of the time-dependent arc voltage revealed differences in the process behaviour for both materials. In case of aluminium welding, a sharp decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Indeed, these comparatively low laser intensities are even found to be much more effective for the stabilization of the arc attachment than the high intensities of the much more focused laser beam used in a previous study, which were causing an increase in arc voltage. 23,24 These results may be regarded as additional proof of our argumentation that the arc stabilization is not caused by the laser-induced evaporation of base material. Instead, it is concluded that the molten surface region within the beam spot region does already offer preferred conditions for arc rooting.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, these comparatively low laser intensities are even found to be much more effective for the stabilization of the arc attachment than the high intensities of the much more focused laser beam used in a previous study, which were causing an increase in arc voltage. 23,24 These results may be regarded as additional proof of our argumentation that the arc stabilization is not caused by the laser-induced evaporation of base material. Instead, it is concluded that the molten surface region within the beam spot region does already offer preferred conditions for arc rooting.…”
Section: Resultssupporting
confidence: 62%
“…[22][23][24] Initially, both heat sources were arranged in a separate order but inclined to each other in such a way that a common operation point of the arc root and the laser spot resulted. The most distinguishing feature of this set-up was the use of a highly focused single-mode fiber laser beam with a focus diameter of only 40 lm and a resultant intensity of 8 Â 10 6 W cm À2 in the case of 100 W applied laser power.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the serious segregation of the materials at these two preparation temperatures, the crack propagation is hindered less, the expansion is faster, which leads to more serious wear and larger debris shedding. When the crack extends to a certain length, the material between the crack and the surface will peel off in the form of flake wear debris [30][31][32][33][34][35][36][37], so the wear mechanism at this time is peeling wear.…”
Section: Friction and Wear Properties Of In-situ Formed Aluminum Matrmentioning
confidence: 99%
“…Here, the laser-induced plasma results in the formation of a so-called keyhole, which allows an improved stirring of the molten material as well as a significant increase in welding depth and thus a larger and more homogenous welding seam [4,5]. In this context, laser irradiation can also be added to plasma arc welding processes in order to improve the process performances [6,7]. The plasmas used for this purpose are usually high-energetic arc discharges, driven at several amperes, where the metallic work piece itself acts as counter electrode.…”
Section: Introductionmentioning
confidence: 99%